Comparison of Hook and Straight Steel Fibers Addition on Malaysian Fly Ash-Based Geopolymer Concrete on the Slump, Density, Water Absorption and Mechanical Properties - Faris, Meor Ahmad (Materials (Basel), 2021)
Geopolymer concrete has the potential to replace ordinary Portland cement which can reduce carbon dioxide emission to the environment. The addition of different amounts of steel fibers, as well as different types of end-shape fibers, could alter the performance of geopolymer concrete. The source of aluminosilicate (fly ash) used in the production of geopolymer concrete may lead to a different result. This study focuses on the comparison between Malaysian fly ash geopolymer concrete with the addition of hooked steel fibers and geopolymer concrete with the addition of straight-end steel fibers to the physical and mechanical properties. Malaysian fly ash was first characterized by X-ray fluorescence (XRF) to identify the chemical composition. The sample of steel fiber reinforced geopolymer concrete was produced by mixing fly ash, alkali activators, aggregates, and specific amounts of hook or straight steel fibers. The steel fibers addition for both types of fibers are 0%, 0.5%, 1.0%, 1.5%, and 2.0% by volume percentage. The samples were cured at room temperature. The physical properties (slump, density, and water absorption) of reinforced geopolymer concrete were studied. Meanwhile, a mechanical performance which is compressive, as well as the flexural strength was studied. The results show that the pattern in physical properties of geopolymer concrete for both types of fibers addition is almost similar where the slump is decreased with density and water absorption is increased with the increasing amount of fibers addition. However, the addition of hook steel fiber to the geopolymer concrete produced a lower slump than the addition of straight steel fibers. Meanwhile, the addition of hook steel fiber to the geopolymer concrete shows a higher density and water absorption compared to the sample with the addition of straight steel fibers. However, the difference is not significant. Besides, samples with the addition of hook steel fibers give better performance for compressive and flexural strength compared to the samples with the addition of straight steel fibers where the highest is at 1.0% of fibers addition.